Readiness for autonomy among CFL learners: a Malaysian perspective - Xi, Mizhe; Fang, Ng Chwee; Abdul Jabar, Mohd Azidan; Jalaluddin, Ilyana (Academy Publication, 2024)
Learner autonomy is paramount in 21st-century education, representing a crucial qualification for lifelong learning. In the area of Chinese as a second/foreign language (CSL/CFL), it is also an important objective of curriculum instruction. However, there is a dearth of empirical research on learner autonomy in a wide range of cultural contexts and distinct domains of language use, especially in the context of CFL. This study aims to scrutinize the readiness for autonomy of CFL learners within the Malaysian settings. The research utilized a quantitative approach to analyze the data. A closed-ended questionnaire survey was conducted with 600 participants. Specifically, the data were synthesized through descriptive statistical analysis to concretely consider the respondents' readiness for learner autonomy in terms of perception of responsibility, assessment of ability, and engagement in the activities in Chinese learning. Findings indicated that Malaysian CFL learners demonstrated a medium readiness for autonomy in Chinese learning. While participants exhibit a relatively high perception of responsibility for autonomous learning, their ability to assess autonomy in decision-making within Chinese learning is somewhat unsatisfactory. Additionally, they express less enthusiasm about engaging in autonomous learning activities inside and outside the classroom. The current study illuminates theoretical and practical dimensions concerning the readiness for autonomy in Chinese learning among Malaysian CFL learners. Moreover, it is anticipated to offer implications for further studies on autonomy development among CFL learners in analogous contexts.